A novel forensic DNA profiling technique for protected species. (December 2015) - Ciavaglia, S.; Donnellan, S.; Tobe, S.; Henry, J.; Linacre, A.
Abstract: Geographic assignment of an unknown sample is a key aim in wildlife forensic science. In the course of examining 28 hypervariable STR loci for this purpose, a locus (MsF14) was observed that routinely exhibited variable amplification efficacy, appearing heritable in a Mendelian manner and reproducible. A correlation was seen between efficacy of amplification and geographic origin using 155 samples from across the species' native range. We propose that this STR locus shows potential to assist in the geographical assignment of an unknown python sample.